(untitled) (Plant Tissue Culture and Biotechnology, 2016)
Five wheat genotypes and their hybrids under four salinity (sea water) levels were considered for tissue culture and randomly amplified polymorphic DNA (RAPD). The genotypes and the hybrids differed in their ability to callus induction, callus fresh weight and regeneration. Among the genotypes, Sakha 93 (P1) followed by Line WB19 (P5) was the most tolerant genotypes for salinity and gave the highest growth rate (46.6%) and (46.3%), respectively while Giza 168 (P3) was the most sensitive one to salinity with lowest growth rate (26.6%). All hybrids scored higher averages in callus growth rate than their parents. P1 × P5 followed by P1 × P2 and P1 × P4 produced the highest growth rate 75.6, 59.1 and 52.6% over hybrids while P3 × P4 had the lowest rate 28.5%, respectively. The hybrid P1 × P5 gave the highest percentage of plant regeneration over all genotypes and their hybrids followed P2 × P5, P1 × P2 and P4 × P5. The highest number of RAPD specific markers scored for hybrid P1 × P5 was (6 markers), while Line WB19 (P5), P1 × P2 and P2 × P5 were (4 markers). These markers can be verified as the RAPD markers associated with salt tolerance. Plant Tissue Cult. & Biotech. 26(1): 25-36, 2016 (June)